Critical analysis of discourse as a methodology for understanding ideologies - Núñez, Javier (2019)
The objective was to evaluate the impact of teaching critical discourse analysis as a methodology for understanding ideologies on students of Sociology at the Universidad Nacional del Altiplano Puno, 2018. This topic is framed within the framework of critical literacy, which refers to the development of competence to read adequately the ideologies of discourses. Groups "A" (control group) and "B" (experimental group) of the second semester formed the study population. To collect the data the rubric was used. The research objective was achieved through the use of the statistical technique Difference in differences. The results suggest that the students of the experimental group improved the level of understanding of ideologies by an average of 5 points as opposed to the students of the control group. This is statistically significant at a level of 99% confidence. Therefore, it is concluded that teaching critical discourse analysis and critical literacy has a positive impact on the understanding of ideologies.